The Effect of Psychological Capital on Work Engagement of Nurse at Pertiwi Hospital in Makassar City - Syam, Rahmawati; Arifin, Nur Afni Indahari (Program Pascasarjana Universitas Negeri Makassar, 2021)
One of the professions that requires high work engagement is a nurse. Psychological capital is one of the factors that can influence a person to feel more attached to the work being done. This study aims to determine whether there is an effect of psychological capital on work engagement of nurses at Pertiwi Hospital Makassar City. The definition of psychological capital in this study uses the theory from Luthans (2007) and work engagement uses the theory from Schaufeli & Bakker (2002). This research was conducted on 71 nurses who worked at Pertiwi Hospital Makassar. The sampling technique used by researchers is cluster random sampling. The data collection tool in this study used a questionnaire in the form of the PsyCap Questionnaire scale to measure psychological capital (PCQ) and the Utrech Work Engagement Scale (UWES) to measure work engagement. Based on research conducted at Pertiwi Makassar Hospital, it can be concluded that psychological capital has a significant positive effect on work engagement, namely high psychological capital will increase work engagement. On the other hand, a low psychological capital will cause a low work engagement.